American law from a Catholic perspective: through a clearer lens - Rychlak, Ronald J. (Catholic social thought, 2015)
Religion and Roman Catholicism in American legal history / Michael Ariens -- The ethics of lawyers and judges : perspectives from Catholic social teaching / Robert A. Destro -- A brief history of American Catholic legal education : the arc of an uncertain identity / John M. Breen and Lee J. Strang -- Philosophy of law / Robert P. George -- Tort law from a Catholic perspective / Ronald J. Rychlak -- American corporate law and Catholic social thought / John M. Czarnetzky -- The meaning of person : a Catholic legal perspective / Robert John Araujo, S.J. -- Church and state / Richard S. Myers -- First Amendment freedoms and the right of privacy : the necessary connection between rights and human dignity that the U.S. Supreme Court often fails to make / Stephen M. Krason -- Equal protection, free speech, and religious worship / Timothy J. Tracey -- United States immigration law and policy through a Catholic lens / Micheal A. Scaperlanda -- Human dignity and the death penalty : comparing Catholic social teaching and Eighth Amendment jurisprudence / Dorie Klein -- Fidelity and fairness In marital commitments, covenants, and contractual relationships : Mulieris Dignitatem's Wisdom / Kevin H. Govern -- Catholic perspectives on family law / Bill Piatt -- The odd couple : comparing U.S. military law and Roman Catholic ideology / Richard V. Meyer -- Property law / D. Brian Scarnecchia -- The call to stewardship : a Catholic perspective on environmental responsibility / Lucia A. Silecchia -- American bankruptcy law and Catholic social theory / John M. Czarnetzky -- Intellectual property / Thomas C. Berg -- Labor and employment law / David L. Gregory -- International human rights, Catholic social teaching, and American practice : the case of human rights treaty committees / William L. Saunders -- Looking back, looking ahead : a strategy for the pro-life movement / Hadley Arkes